Avaliação de marcadores internos para estimativa de fluxo de digesta e proteína microbiana no duodeno de ruminantes - Stefanello, Cristiano Miguel (2014)
The aim of this study was to evaluate the use of internal markers to estimate duodenal flow of digesta and duodenal microbial protein synthesis in cattle and sheep. Data and samples of in vivo digestibility trials, eight trials with sheep (n=204) and two with cattle (n=31) were used. All animals were cannulated in the duodenum, procedure previously conducted at the Laboratory of Food Science and Ruminants Nutrition at the Federal University of Santa Maria and Laboratory of Animal Nutrition and Food Science at the University of the State of Santa Catarina. Internal markers, acid detergent fiber (ADF) and acid detergent lignin (ADL) were compared to estimate the flow of duodenal digesta. Purines in duodenal digesta were compared with purine derivatives (PD) excreted in urine as markers to estimate the flow of rumen microbial protein in the duodenum. In the latter case, different equations available in literature were tested to estimate the flow of microbial protein from urinary PD. It was concluded that ADF may be used as an internal marker to estimate duodenal flow of digesta in experimental animals cannulated in the duodenum where total fecal excretion is measured, and that the use of DP as a marker of duodenal flow of microbial protein is acceptable for cattle but not for sheep. In sheep, regardless of the equation used, the DP underestimated duodenal availability of rumen microbial protein.